Failure to disrupt : why technology alone can't transform education - Reich, Justin, 1977- (Harvard University Press, 2020)
"From MOOCs to autograders to computerized tutors, technologies designed for large-scale learning have never lived up to the hype. Justin Reich once promoted these "transformative" novelties; now he reveals their failures. Successful education reform, he concludes, will focus on incremental institutional change, not the next killer app"--